The Influence of The Contextual Teachıng Learnıng (CTL) Learnıng Model on the Learnıng Outcomes of Social Sciences Natural Resources Materıal Class IV SDN Jepara I/90 - Savitri Suryandari; Friendha Yuanta (Universitas Nahdatul Ulama Surabaya, 2023)
This research aims to describe the influence of the Contextual Teaching Learning (CTL) learning model on the social studies learning outcomes of class IV students at SDN Jepara I/90 Surabaya. The aim of this research is the need for efforts to improve the quality of student learning processes and outcomes. The social studies learning process that only uses learning resources from books and is not interactive can have an impact on student learning outcomes that are not optimal. The approach used is a quantitative approach with experimental research. The research design used is Quasi Experimental Design. The population used in this research was 72 students and the research sample was 36 students. In collecting the data used were multiple choice test questions. The test technique used by children is pretest-posttest to determine learning outcomes. Based on data analysis, it was concluded: 1) The results of data analysis showed that the average learning outcome value for the experimental class was 98.75 and the control class was 78.75. 2) the results of the hypothesis test using the T test show that the results of the hypothesis test for pairs 1 and 2 reject Ho and accept Ha with a sig value. 2 Tailed 0.000 < 0.05 with this there is an influence of the CTL Learning Model on the learning outcomes of class IV students at SDN I/90 of 39,696